(untitled) (Revista de História Regional, 2007)
The article intends to approach the operational structure of the Corpos de Ordenanças analysing their organizational and legislative bases. Approaching the case of Minas Gerais, we will also try to analyze the character of these corps, their hierarchy, contingent and disposition of troops for the district of Vila Rica, between 1735-1777. We also try to demonstrate the importance of the relationships that these officials established with the slaves for the structuring and enlargement of their command power, since this should be allowed by such social segments.